Validation of a grounded theory of nurse bullying in emergency department settings. (May 2021) - Wolf, Lisa A.; Perhats, Cydne; Delao, Altair M.; Martinovich, Zoran
Highlights: Workplace bullying in health care settings is a significant and negative factor in the dynamics of patient care and nursing work culture. Workplace bullying has a significant impact on nurse retention. Workplace bullying may result in symptoms of secondary traumatic stress. This model of workplace bullying in emergency settings is theoretically coherent and may be used to design interventions. Abstract: Background: Workplace bullying in health care settings, including emergency departments (EDs), is a significant and negative factor in the dynamics of patient care, nursing work culture, and nurse retention. Specifically, workplace bullying has a significant and negative effect on patient care, with both direct (errors and substandard care) and indirect sequelae (high turnover and inexperienced nursing staff hired to replace those nurses who have left to escape bullying behavior). The purpose of this study was to determine the theoretical coherence of the ENA model of nurse bullying in emergency department and its impact on emergency nurses' intent to leave their job. Methods: Correlational study using the Practice Environment Scale of the Nursing Work Index (PES-NWI), the Secondary Traumatic Stress Scale (STSS), and the Short Negative Acts Questionnaire (SNAQ) in a cross-sectional sample of emergency nurses working in the United States. Results: Extremely high intent to leave the current ED (PD1) rates were associated with nurses' reported exposure to daily bullying (PD1 rate = 67.6%, zero-order OR = 4.77, Nr 2  = 3.2%, p < .001) and bullying multiple times per week (49.1%, zero-order OR = 2.31, Nr 2  = 2.6%, p < .001). Nurses who reported no exposure to bullying at work had a distinctly below average PD1 rate (22.9%, OR = 0.47, Nr 2  = 3.9%, p < .001). Conclusions: The relationships between the tested elements of the model (specifically, the influence of bullying on nurse intent to leave) as constructed appear to adequately reflect the phenomenon of workplace bullying and its effects on nurse retention in emergency care settings.